Mepacrine accumulation during treatment of chloroquine-resistant falciparum malaria. - Looareesuwan, S; Phillips, R; Edwards, G; Rodick, C; Chanthavanich, P; Supanaranond, W; Warrell, D (1988)
Oral mepacrine dihydrochloride, 200 mg (158 mg of the base) six-hourly for five doses followed by 100 mg (79 mg of the base) eight-hourly for six days (half dosage for those less than or equal to 50 kg) was given to 21 patients with high-grade chloroquine-resistant falciparum malaria in eastern Thailand. Fifteen patients (71%) had a clinical response [fever clearance time of 81 +/- 35 hours (mean +/- S.D.)] and 13 (62%) had complete clearance of parasitaemia (clearance time 92 +/- 42 hours). Two patients were cured, but 11 patients returned with recurrent parasitaemia between 11 and 40 days after starting treatment. Five patients had an R2 response and three had an R3 response. Mepacrine retains some activity against chloroquine-resistant falciparum malaria but it cannot be recommended for use in Thailand. The doses used, which are those also recommended for giardiasis, led to progressive and potentially toxic mepacrine accumulation. Further evaluation of regimens which produce safer plasma concentration profiles is needed.